Analysis of the Sale and Purchase of Goods from the Seller from the Perspective of Sharia Economic Law (Study at the Cahaya Baru Bangun Rejo Shop, Central Lampung) - Tutur Astuti; Linda Firdawaty; Susi Nurkholidah (al-Afkar, Journal For Islamic Studies, 2026)
The unstable price fluctuations of basic necessities indicate the potential for market distortion, one of which is the practice of hoarding (ihtikar), which can be detrimental to society. This condition raises questions regarding the compliance of this practice with the principles of Islamic economic law. This study formulates the problem of how the practice of buying and selling hoarded goods is carried out by sellers and how to analyze it from the perspective of Islamic economic law. This study aims to analyze this practice and assess its compliance with the principles of justice, transparency, and welfare. The method used is field research with a qualitative descriptive approach, through observation, interviews, and documentation techniques at the Cahaya Baru Bangun Rejo Store, Central Lampung. The results show that sellers purchase goods in large quantities when prices are low, then store them for resale when prices increase, which results in price increases and consumer burdens. This practice is also accompanied by a lack of price transparency. Based on the analysis, this practice points to indications of ihtikar, which is inconsistent with the principles of Islamic economic law because it contains elements of injustice and is detrimental to society.